2016
DOI: 10.1038/s41551-016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the foreign body response to biomaterials by nonlinear intravital microscopy

Abstract: Implanted biomaterials often fail because they elicit a foreign body response (FBR) and concomitant fibrotic encapsulation. To design clinically relevant interference approaches, it is crucial to first examine the FBR mechanisms. Here, we report the development and validation of infrared-excited nonlinear microscopy to resolve the three-dimensional (3D) organization and fate of 3D-electrospun scaffolds implanted deep into the skin of mice, and the following step-wise FBR process. We observed that immigrating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
168
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(184 citation statements)
references
References 57 publications
(89 reference statements)
3
168
1
Order By: Relevance
“…We focused our 9 attention on macrophages (CD68 + CD11b + ) and other myeloid cells (CD68 -Gr1 low/-CD11b + ) that were predominant fractions of immune cells sorted by FACS (Figure 4, S-4). Macrophages are especially relevant in this context since they display remarkable functional plasticity and participate in the host defence, immune regulation, and tissue repair, all aspects playing a pivotal role in mediating implant-triggered fibrosis 3,34,35 .…”
Section: Muc-gel Implants Dampened the Macrophage And Myeloid Cell Acmentioning
confidence: 99%
“…We focused our 9 attention on macrophages (CD68 + CD11b + ) and other myeloid cells (CD68 -Gr1 low/-CD11b + ) that were predominant fractions of immune cells sorted by FACS (Figure 4, S-4). Macrophages are especially relevant in this context since they display remarkable functional plasticity and participate in the host defence, immune regulation, and tissue repair, all aspects playing a pivotal role in mediating implant-triggered fibrosis 3,34,35 .…”
Section: Muc-gel Implants Dampened the Macrophage And Myeloid Cell Acmentioning
confidence: 99%
“…46 The bone implants often fail in the osteolysis and aseptic loosening induced by prolonged inflammatory response around the implant materials. [48][49][50] The proinflammatory mediators including IL-6 and TNF-α are often found at the implantation site. Macrophages are one of the inflammatory cells accepted as a crucial source of inflammatory signals.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are one of the inflammatory cells accepted as a crucial source of inflammatory signals. [48][49][50] The proinflammatory mediators including IL-6 and TNF-α are often found at the implantation site. 47 A recent study found that titanium with smooth morphology expressed a higher mRNA level of IL-6 and TNF-α compared with the rough surface.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced insight into the processes that contribute to successful repair therefore requires a method for nondestructive, high‐resolution visualization of bone tissue–engineered constructs in vivo. A promising approach for the study of living tissue exists in the combination of intravital microscopy with multiphoton fluorescence excitation, which is increasingly being applied to investigate tumor biology and host reactions on implanted biomaterials …”
Section: Introductionmentioning
confidence: 99%
“…A promising approach for the study of living tissue exists in the combination of intravital microscopy with multiphoton fluorescence excitation, which is increasingly being applied to investigate tumor biology and host reactions on implanted biomaterials. (5,6) Multiphoton-intravital microscopy (MP-IVM) relies on the nonlinear excitation of fluorophores through absorption of two or more photons at once. (7) This means that near-infrared excitation wavelengths can be used which penetrate deeper into the tissue, result in less off-target phototoxicity, and allow the label-free visualization of collagen fibrils through secondharmonics generation.…”
Section: Introductionmentioning
confidence: 99%